Simple definition of error probability at binary signaling over generalized channels - V. P. Tuzlukov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The performance of binary signaling on generalized fading channels with maximal ratio combining (MRC) and imperfect channel estimates is studied. It is assumed that estimates of the communication channel parameters are distorted by interference, which is a complex Gaussian random variable. An expression for the average probability of error is provided in the form of a simple single integral which involves the moment generating function of the normalized signal-to-noise ratio corresponding to the case of ideal MRC. Various examples demonstrate the usefulness of the derived expression under various fading conditions with different distributions and with a possible correlation between the diversity branches.